Pengembangan Kapasitas (Capacity Building ) dalam Mendukung Pelaksanaan Otonomi Daerah - Drs. Nugraha Drs. Nugraha (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
A capacity building is a serious attempt of an organization to develop its performance capability — the ability to apply skills and resources successfully in order to accomplish the objectives and satisfy stakeholders’ expectations.Studies by UNDP found out that the concept of capacity building is considered to be the right choice of local government to support the implementation of autonomy policy. This paper will discuss deeply the nine strategies of developing capacity building to be implemented in the local government level.